Investigation on the Behavior of Tensile Damage Evolution in T700/6808 Composite Based on Acoustic Emission Technology - Weihan Wang; Weifang Zhang; Shengwang Liu; Xiaoshuai Jin (Shock and Vibration)
T700/6808 composite has been widely used in aerospace field and the damage in composite will seriously influence the safety of aircraft. However, the behavior of damage evolution in T700/6808 composite when it suffered from tensile loading is seldom researched. In this paper, the acoustic emission (AE) technology is employed to research the process of damage evolution in T700/6808 composite under tensile loading. Results show that the damage in T700/6808 composite is small in the initial stage of tensile loading, and main damage is the matrix cracking. The composite has serious damage in the middle stage of tensile loading, which mainly includes the matrix cracking and the interface damage as well as the fiber breakage. The number of fiber breakages decreases rapidly in the later stage of tensile loading. When it comes into the stage of load holding, the composite has relatively smaller damage than that in the stage of tensile loading, and the fiber breakage rarely occurs in the composite. Analysis of damage modes shows that the criticality of the matrix cracking and the interface damage is higher than the fiber breakage, which illustrates that the reliability of T700/6808 composite could be improved by the optimization of matrix and interface.